FEWSG DAM (Flood = Electricity + Water + Storage + Solar Garbage Trapper) DAM / Siti Nurul Syazwani Mohd Radzi ... [et al.] - Mohd Radzi, Siti Nurul Syazwani; Fadli Fizari, Ar-Rayyan Fikri; Mat Saad, Azlina; Abu Hassan Asari, Fadli Fizari (2018)
During heavy rainfall, low-lying places may face flood and storm water. Instead, it can cause runoff and eroding soil, thus, leading to another unwanted abundance garbage. However, every problem creates an opportunity. This paper proposes how flood can be manipulated as a source of clean water and renewable electricity. Mini turbine and solar trap technologies allow it to operate in a limited space, especially in traditional villages. At the same time, excess treated flood water can be stored underground for a future use. This green technology may give new hope to those who are often hit by flood problems over the years.